Job Vacancy Survey as a Tool of Labour Market Information in Developing Countries - Mehmet, Ozay (Relations industrielles / Industrial Relations, 1971)
The purpose of this article is to present an operational method for collecting systematic data about current manpower demand. This method was originally developed in Malaysia, where it is now being implemented as a regular programme in the Ministry of Labour.